Steam reforming of n-hexadecane over noble metal-modified Ni-based catalysts - Kim, Dae Hyun; Kang, Jung Shik; Lee, Yun Joo; Park, Nam Kuk; Kim, Young Chul; Hong, Suk In; Moon, Dong Ju (ELSEVIER, 2008)
Steam reforming of n-hexadecane, a main constituent of diesel, over noble metal-modified Ni-based hydrotalcite catalyst was carried out in a temperature range of 700-950 degrees C, at an atmospheric pressure with space velocity of 10,000-100,000 h(-1) and feed molar ratio of H2O/C = 3.0. The catalysts were prepared by a co-precipitation and dipping methods. The noble metal-modified Ni-based hydrotalcite catalyst displayed higher resistance for the sintering of active metal than the Ni-based hydrotalcite catalyst prepared by the conventional method. It was found that the Rh-modified Ni-based catalysts showed high resistance to the formation of carbon compared to Ni-based catalysts. The results suggest that Rh-modified Ni-based catalyst can be applied for the steam reforming (SR) reaction of diesel. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: MG-AL HYDROTALCITE; PHASE CRYSTALLIZATION METHOD; PARTIAL OXIDATION; LOADED CATALYST; FUEL; HYDROGEN; METHANE; CH4; GASOLINE; RU